Analysis of Students’ Diagrams Explaining Scientific Phenomena - McLure, Felicity; Won, Mihye; Treagust, David (2021)
While there has been much interest in the power of student-generated multiple representations to promote student reasoning and conceptual understanding, most studies of student explanations have been of written artefacts or only included diagrams as an adjunct to written explanations. This approach may be because teachers do not have an accessible framework with which to evaluate students’ diagrams as being explanations. Adapting de Andrade et al.’s Research in Science Education, 49, 787-807 (2019) evaluation framework for written explanations, this study explored the benefits and limitations of a framework to evaluate students’ explanatory diagrams. Seventeen grade 5 and 6 students produced a series of explanatory diagrams over six chemistry lessons on particle theory. Their diagrams were coded and evaluated using the proposed diagram analysis framework. Some sample diagrams are included to illustrate how the framework assisted the evaluation of students’ diagrams. The framework helped identify key features of students’ diagrams and evaluate their explanatory powers consistently and effectively. This research also indicates that a series of stand-alone diagrams can effectively be used by teachers to assess how students communicate their understanding of causal explanations in terms of sub-microscopic entities of the underlying phenomena.